Longitudinal Changes Over 10 Years in Free Testosterone Among HIV-Infected and HIV-Uninfected Men. (1st January 2016) - Slama, Laurence; Jacobson, Lisa P.; Li, Xiuhong; Palella, Frank J.; Margolick, Joseph B.; Kingsley, Lawrence A.; Wiley, Dorothy J.; Pialoux, Gilles; Dobs, Adrian S.; Brown, Todd T.
Abstract : Background: Aging in males is associated with lower testosterone levels and a decrease in diurnal variation of testosterone secretion. Cross-sectional studies have shown lower than expected testosterone levels among HIV-infected men, but whether age-related changes in serum testosterone differ by HIV serostatus are not known. Methods: HIV-infected men from the Multicenter AIDS Cohort Study (MACS), age ≥45 years at highly active antiretroviral therapy initiation, who had ≥2 samples from the subsequent 10 years, were matched to HIV-uninfected men by age, race, MACS site, and calendar time of samples. Linear mixed-effects regression models were used to determine whether free testosterone (FT) and its rate of change differed by HIV serostatus. Results: One hundred eighty-two HIV-infected and 267 HIV-uninfected men were included, median age: 48.8 years (interquartile range: 45.8–53.4), median numbers of FT measurements per participant 4 (interquartile range: 3–5), 65% were drawn in the adjusted morning (AM). Mean-adjusted FT levels were lower among HIV-infected than HIV-uninfected men in AM samples −6.1 ng/dL [95% confidence interval (CI): −9.8 to −2.4], P = 0.001, but not in afternoon samples [−1.7 ng/dL (−6.0 to 2.6), P = 0.441]. The rate of FT decline with age did not differ by HIV serostatus: 9.2 ng/dL (95% CI: −13.4 to −5.0) per 10 years for HIV-infected vs. 7.9 ng/dL (95% CI: −10.2 to −5.5) for HIV-uninfected men, P = 0.578. Conclusions: FT decreased similarly with increasing age regardless of HIV serostatus. The lower AM, but not adjusted afternoon, FT levels among HIV-infected men compared with HIV-uninfected men suggest a loss of diurnal variation in FT levels among HIV-infected men.